J e (4.2 K, 31.2 T) beyond 1 kA/mm2 of a ~3.2 μm thick, 20 mol% Zr-added MOCVD REBCO coated conductor - A. Xu (Nature Portfolio, 2017)
Abstract A main challenge that significantly impedes REBa2Cu3Ox (RE = rare earth) coated conductor applications is the low engineering critical current density J e because of the low superconductor fill factor in a complicated layered structure that is crucial for REBa2Cu3Ox to carry supercurrent. Recently, we have successfully achieved engineering critical current density beyond 2.0 kA/mm2 at 4.2 K and 16 T, by growing thick REBa2Cu3Ox layer, from ∼1.0 μm up to ∼3.2 μm, as well as controlling the pinning microstructure. Such high engineering critical current density, the highest value ever observed so far, establishes the essential role of REBa2Cu3Ox coated conductors for very high field magnet applications. We attribute such excellent performance to the dense c-axis self-assembled BaZrO3 nanorods, the elimination of large misoriented grains, and the suppression of big second phase particles in this ~3.2 μm thick REBa2Cu3Ox film.